REAP: ring band-based energy adaptive protocol for information dissemination and forwarding in wireless sensor networks. (7th September 2006) - Li, Guanfeng; Znati, Taieb; Gopalan, Anandha
The design issues related to routing in Wireless Sensor Networks (WSNs) are inherently different from those encountered in traditional mobile ad hoc networks. Routing protocols for adhoc networks usually impose prohibitive demands on scares resources of a sensor node such as memory, bandwidth and energy; therefore, they are not suitable for WSNs. In this paper, we present a novel, energy adaptive data forwarding protocol, referred to as Ring band-based Energy Adaptive Protocol (REAP), in which nodes self-organise into virtual ring bands centred at the Base Station (BS). Packets are automatically delivered to the BS along a path with decreasing ring band number. Furthermore, the proposed probabilistic forwarding mechanism also balances the workload among neighbouring nodes within the same ring band. Simulation study showed REAP exhibits good performance in various network settings even when nodes are in rapid motion.